Influence of workplace incivility on the quality of nursing care - Alshehry, Abdualrahman Saeed; Alquwez, Nahed; Almazan, Joseph; Namis, Ibrahim Mohammed; Cruz, Jonas Preposi (WILEY, 2019)
Aims and objectives To examine the influence of workplace incivility on the quality of nursing care. Background Recent evidence describes workplace incivility as a serious concern in the healthcare setting worldwide. Exposure to workplace incivility can alter a nurse's behaviour, thought process and perspective towards the nursing profession. However, there is insufficient evidence to determine whether workplace incivility might be associated with the quality of nursing care in Saudi Arabia. Design A quantitative and cross‐sectional study. Method A survey was carried out amongst 378 nurses in two government hospitals in Saudi Arabia from February 2018–May 2018 using the Nurse Incivility and quality of nursing care scales. Multivariate multiple regression was performed to investigate the influence of the uncivil experiences of nurses from different sources on the different aspects of quality of nursing care. The study adhered to STROBE guideline (see Appendix S1). Results The overall mean of the quality of nursing care scale was 3.14 (SD = 0.66) from a scale of 1–5, with patient satisfaction receiving the highest mean dimension (mean = 3.27, SD = 0.72) and health promotion the lowest mean dimension (mean = 3.08, SD = 0.74). Experience in the present hospital and the hospital were associated with the overall quality of nursing care. General and nurse incivility exerted a multivariate effect on overall quality of nursing care and its different dimensions. Conclusion General incivility and nurse incivility were found to negatively impact quality of nursing care and its different dimensions. Relevance to clinical practice Stronger policies geared towards eliminating workplace incivility should be implemented as uncivil acts can lead to poor quality of nursing care. Nurse administrators and nurses should be pro‐active in recognising, preventing, approaching, reporting and intervening with uncivil acts in the hospital to protect these workers from these types of behaviours and avoid their negative impacts on patient care.
https://onlinelibrary.wiley.com/doi/epdf/10.1111/jocn.15051
Keywords: incivility; nurses; nursing care; quality of nursing care; Saudi Arabia